2013
DOI: 10.1007/s11999-012-2636-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Technique: Endoscopic Gluteus Maximus Tendon Release for External Snapping Hip Syndrome

Abstract: Background While many authors have recommended surgery for patients with persistent symptoms of external snapping hip, it is unclear which one best relieves symptoms. Concerns with iliotibial band (ITB)-modifying techniques include altering the shape of the lateral thigh and overload of the contralateral abduction mechanism. We describe a new endoscopic technique that decreases the tension of the ITB complex by releasing the femoral insertion of the gluteus maximus tendon (GMT). Description of Technique Via an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 12 publications
0
77
0
Order By: Relevance
“…Surgical treatment is indicated when patients do not respond to conservative treatments. Many surgical techniques have been reported in literature for the treatment both for ESHS and ISHS ( In order to preserve the abductor complex, Polesello et al [25] proposed the release of the gluteus maximum tendon (GMT), based on the hypothesis that the ITB, the gluteus maximum (GM) and the tensor fascia late (TFL) muscle work as a single complex. In fact, the ITB is pulled by the TFL anteriorly, and by the GM posteriorly, which work in synergy, and they are currently considered the main responsible of ESH [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical treatment is indicated when patients do not respond to conservative treatments. Many surgical techniques have been reported in literature for the treatment both for ESHS and ISHS ( In order to preserve the abductor complex, Polesello et al [25] proposed the release of the gluteus maximum tendon (GMT), based on the hypothesis that the ITB, the gluteus maximum (GM) and the tensor fascia late (TFL) muscle work as a single complex. In fact, the ITB is pulled by the TFL anteriorly, and by the GM posteriorly, which work in synergy, and they are currently considered the main responsible of ESH [33].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of surgery is to release the tendon to resolve the snapping. Different surgical procedures have been reported for treatment of ESH, including Zshaped ITB release, formal Z-lengthening, cross-shaped release, or the release of the gluteus maximus tendon insertion to the femur, which can be performed both open or endoscopically [21][22][23][24][25]. An open Zlengthening procedure was performed by Provencher, et al [21] they reported on 9 cases (8 patients) with a complete resolution of symptoms, and all but 1 returned back to active military duty.…”
Section: Conservative Management Of Eshsmentioning
confidence: 99%
See 1 more Smart Citation
“…External coxa saltans or external snapping hip can occur as a result of a thickening of the posterior ITB, the TFL, or the gluteus maximus as they slide over the greater trochanter during hip flexion [31][32][33][34]. This frictional irritation may also lead to GTB [31].…”
Section: External Snapping Hipmentioning
confidence: 99%
“…Imaging consists of x-rays of the pelvis to exclude other pathologies causing hip pain [32,33,35]. Ultrasound and MRI may complement the history and physical exam but are probably unnecessary, except for cases in which there is concern for additional pathologies [35].…”
Section: External Snapping Hipmentioning
confidence: 99%